Effects of different surface treatments of zirconia on the bond strength of self-adhesive resinous cement - Zanatta, Rayssa Ferreira [UNESP]; Esper, Maria Ângela Lacerda Rangel [UNESP]; Pucci, Cesar Rogério [UNESP]; Borges, Alessandra Bühler [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Taylor & Francis, 2017)
Purpose: The aim of this study was to evaluate the effects of different zirconia surface treatments on the bond strength of two self-adhesive resinous cements (SARC). Methods: Two hundred and eight cylindrical specimens were obtained from Y-TZP zirconia (half with diameter 3.2 mm and half with 4.8 mm). After sintering and polishing, specimens were divided into four groups (n = 26), according to surface treatment: Control (no treatment); Sandblasting (Al2O3 particles); Rocatec (Al2O3 particles, tribochemical silica coating and silane application); Laser (Nd: YAG laser: 20 Hz, 100 mJ, 0.2 J/cm²). The surface roughness (Ra) was evaluated after the surface treatments, and the groups were divided into two subgroups (n = 13), according to the SARC tested: RelyX U200 and Bifix SE. The 2.2-mm cylinders were bonded to 4.8-mm cylinders and stressed until failure under shear using a universal testing machine. Bond strength and Ra were analyzed using ANOVA, and Tukey’s test (α = 0.05). Results: Surface treatment was significant (p < 0.0001), but cement type (p = 0.73) was not. Related to roughness, significant differences were found for the treatment type (p < 0.0001), with laser being the treatment with higher Ra values. Conclusions: Nd:YAG laser produced a rougher surface and a higher bond strength compared with sandblasting, silicatization, and control groups.
Keywords: bond strength; Nd:YAG Laser; self-adhesive cement; surface treatments; Zirconia